Penerapan Model Snowball Throwing dalam Upaya Meningkatkan Keaktifan Siswa pada Pembelajaran IPS Kelas V di MI NU Miftahul Huda 01 Karangmalang - Amalia Khamidah; Eva Luthfi Fakhru Ahsani; Khalimatul A'isah (Jurnal Riset Madrasah Ibtidaiyah, 2023)
The main problem of this research is the learning process that still uses the lecture method in social studies learning at MI NU Miftahul Huda 01 Karangmalang, Gebog District, Kudus Regency, Central Java so that it influences student activity.  This study aims to apply the Snowball Throwing model to social studies learning about the Indonesian Community's Economic Business for class V at MI NU Miftahul Huda 01 Karangmalang.  Classroom Action Research (CAR) was carried out in two cycles.  The research model uses the Kemmis & MC Taggart research model which consists of four stages, namely planning, implementing, observing, and reflecting.  The subjects in this study were class V for the 2022/2023 academic year with a total of 31 students.  Data collection techniques through observation, interviews, and documentation.  The type of data used is qualitative data.  The results showed that the application of the Snowball Throwing learning model could increase student activity.  The increase occurred in each cycle experiencing an increase of 60.08% in cycle I. In cycle II students were very active in increasing an average of 93.33%.  This proves that the Snowball Throwing learning model can increase social studies learning activity at MI NU Miftahul Huda 01 Karangmalang Class V for the 2022/2023 academic year.